2006
DOI: 10.1186/1747-597x-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management methods for out-patients with alcohol dependence

Abstract: Background: In France outpatient centres for the care of alcoholics are healthcare establishments providing medical, psychological and social support. Although they meet the practical needs of these patients, their degree of use in each of these domains and the respective mobilisation of different skills by the care team are not well understood. Our aim was therefore to determine in detail the management involved as a function of the severity of alcohol dependence. For this purpose, all the procedures involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Our data are consistent with the recent study of Nalpas et al (2006), who described a significant improvement of medical, alcohol, drugs, and psychological domains and a trend of improvement for the social and familiar environment after 3 months of abstinence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are consistent with the recent study of Nalpas et al (2006), who described a significant improvement of medical, alcohol, drugs, and psychological domains and a trend of improvement for the social and familiar environment after 3 months of abstinence.…”
Section: Discussionsupporting
confidence: 93%
“…The present results showed that alcohol abstinence is able to improve several features of addiction severity, including medical (ASI 1), employment (ASI 2), alcohol (ASI 3), legal (ASI 6), and psychiatric (ASI 7) problems. Our data are consistent with the recent study of Nalpas et al ( 2006 ), who described a significant improvement of medical, alcohol, drugs, and psychological domains and a trend of improvement for the social and familiar environment after 3 months of abstinence.…”
Section: Discussionsupporting
confidence: 93%
“…In the third stage, post-withdrawal, the importance of this medical component decreases in favour of psychological and social support (Ouimette et al, 1998). A study of French patients followed up in the Centre for Care, Support and Prevention in Addiction showed that psychologists and social workers were the most active during the patient's time in care (Nalpas et al, 2006). Self-help organizations for people with alcohol problems constituted the third most important source of support (Mueller et al, 2007).…”
Section: Introductionmentioning
confidence: 99%